Pengaruh Akupresure Pericardium 6 Terhadap Mual Muntah Pada Pasien Kanker Serviks Post Kemoterapi - Dyah Nurita Hany; Anis Ardiyanti; Diffa Risqa Arisdiani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cervical cancer is a type of cancer that attacks the cervix in women and can be treated with chemotherapy. One of the side effects of chemotherapy is nausea and vomiting. Nausea and vomiting can be treated by administering Acupressure Pericardium 6. This study aimed to determine the effect of administering Acupressure Pericardium 6 on nausea and vomiting in post-chemotherapy cervical cancer patients. This type of research is quantitative, using a quasi-experimental pre-test and post-test one-group design. The study employed purposive sampling with 47 respondents, utilizing the INVR index measuring instrument. The results of the analysis showed that the majority were elderly, aged 46–65 years (70.2%), elementary school education level (42.6%), non-working employment status (61.7%), type of chemotherapy drug carboplatin (19.1%), and stage III cervical cancer (42.6%). Before receiving the acupressure pericardium intervention, post-chemotherapy patients experienced 6 frequencies of moderate nausea and vomiting (46.8%), and after the intervention, they experienced 6 frequencies of mild nausea and vomiting (44.7%). After that, a statistical test was carried out using the Wilcoxon test, obtaining a p-value of 0.000 or ≤ 0.05. In conclusion, pericardium 6 acupressure has an effect on nausea and vomiting in post-chemotherapy cervical cancer patients. Future researchers should develop variables and pay more attention to the timing of administering Pericardium 6 acupressure to ensure optimal results.